Decreased muscle strength and thigh muscle area assessed with CT imaging in older Chinese adults with long duration of type 2 diabetes - Yuan, Yi; Li, Sidong; Yin, Lu; Su, Yongbin; Guo, Zhe; Liu, Yandong; Blake, Glen M.; Wang, Ling; Liu, Yajun; Cheng, Xiaoguang; Engelke, Klaus; Vlug, Annegreet G. (Journal of Nutrition, Health & Aging, 2025)
Objective: We aimed to compare muscle strength, physical performance, and muscle parameters in non-diabetic and type 2 diabetes mellitus (T2DM) older adults and to determine the association of the duration of diabetes with these outcomes. Design: A cross-sectional study. Setting: The China Action on Spine and Hip Status study (CASH). Participants: 301 participants enrolled from a subcohort of CASH, of which 114 were diagnosed with well-controlled type 2 diabetes mellitus, Measurements: We measured physical performance and muscle strength with the timed up-and-go test (TUG) and handgrip strength (HGS) and measured the area and density of the thigh, gluteus and trunk muscles (core muscles) using quantitative CT scans. Results: Participants with long-term (≥10 years) diabetes had a longer TUG (β coefficient: 0.64 [95% CI, 0.06, 1.22]; P = 0.030) and a lower HGS (−2.29 [−4.48, −0.10]; P = 0.041) as well as a lower muscle area of the thigh (−7.10 [−13.44, −0.76]; P = 0.028). The lower HGS among patients with long-term (≥10 years) diabetes was largely mediated by muscle area of the thigh (compared with non-diabetic controls: percentage mediated, 38.3%; P = 0.023; compared with <10 years diabetes: percentage mediated, 51.8%; P = 0.039). Conclusions: Older adults with long-term (≥10 years) diabetes had lower TUG and HGS than either non-diabetic participants, and the difference in HGS was largely mediated by a decrease in muscle area of the thigh muscles. Our finding suggested that long duration of diabetes, even in well-controlled subjects, may be associated with poor physical functions.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Grip strength; Muscle density; Muscle size; Timed up and go test; Type 2 diabetes